Job satisfaction model for manufacturing industry: focus on ergonomics and human factors in work design - Md Dawal, Siti Zawiah; Taha, Z. (2009)
Effect of work design factors which emphasis on job characteristics, environmental and organization factors on job satisfaction were examined in two manufacturing companies in Malaysia. One hundred and seventy male subjects with the mean age of 26.8 years and mean work experience of 6.5 years were involved. The potential applications of these methods developed namely questionnaire design, data collection and statistical analysis to diagnose current industrial work design factors that affect workers satisfaction. Significant work design factors were determined using regression analysis. The model highlights the most significant attributes in both manufacturing industries that affect workers satisfaction are skill variety, noise, job rotation and work method.